Use of ATP to characterize biomass viability in freely suspended and immobilized cell bioreactors. - Gikas,P; Livingston,AG (Biotechnol Bioeng, 1993)
This work describes investigations into the viability of cells growing on 3,4-dichloroaniline (34DCA). Two bioreactors are employed for microbial growth, a continuous stirred tank (CST) bioreactor with a 2-L working volume, and a three-phase air lift (TPAL) bioreactor with a 3-L working volume. Experiments have been performed at several dilution rates between 0.027 and 0.115 h(-1) in the CST bioreactor and between 0.111 and 0.500 h(-1) in the TPAL bioreactor. The specific ATP concentration was calculated at each dilution rate in the suspended biomass in both bioreactors as well as in the immobilized biomass in the TPAL bioreactor. The ATP was extracted from the cells using boiling tris-EDTA buffer (pH 7.75), and the quantity determined using a firefly (bioluminescence) technique. The cultures were inspected under an electron microscope to monitor compositional changes. Results from the CST bioreactor showed that the biomass-specific ATP concentration increases from 0.44 to 1.86 mg ATP g(-1) dry weight (dw) as dilution rate increases from 0.027 to 0.115 h(-1). At this upper dilution rate the cells were washed out. The specific ATP concentration reached a limiting average value of 1.73 mg ATP g(-1) dw, which is assumed to be the quantity of ATP in 100% viable biomass. In the TPAL bioreactor, the ATP level increased with dilution rate in both the immobilized and suspended biomass. The specific ATP concentration in the immobilized biomass increased from approximately 0.051 mg ATP g(-1) dw at dilution rates between 0.111 and 0.200 h(-1) to approximately 0.119 mg ATP g(-1) dw at dilution rates between 0.300 and 0.500 h(-1). This indicates that the immobilized biomass contained a viable cell fraction of around 5%. Based on these results, kinetic data for freely suspended cells should not be applied to the modeling of immobilized cell systems on the assumption that immobilized biomass is 100% viable.